Influence The Composite Of The Media For The Growth Of Timor-Leste's Hybrid Coffee (Coffee Sp) With Other - Madeira Soares, Mario; de Jesus Gomes , Julio (CV RIFAINSTITUT, 2024)
The aim this investigation was to determine the effect of means composition about to the growth of hybrid Timorese coffee cuttings with other varieties in the prey nursery to the means application for the growth of the four varieties of coffee, thus the write takes the Title of the research with the hypothesis